2019
DOI: 10.1103/physrevb.99.125420
|View full text |Cite
|
Sign up to set email alerts
|

Peak splitting and locking behavior arising from Fano interference between localized surface plasmons and cavity modes

Abstract: Coupling localized surface plasmons (LSPs) in Au nanostructure arrays to Fabry-Pérot cavity modes, both peak splitting and peak locking behaviors can be observed when light is incident normally into the cavity from different directions. These phenomena can be quantitatively described by a model based on modified Fresnel equations, and thus be interpreted as an extended Fano resonance effect. Both the peak splitting and peak locking behaviors arise from the interference between localized surface plasmon resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…There are almost no polarization charges between these two surfaces. Thus, by regarding the top and bottom surface of the nanocube arrays as two equivalent interfaces with different frequency-dependent polarizability, thin film interference calculations can be established using modified Fresnel equations [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…There are almost no polarization charges between these two surfaces. Thus, by regarding the top and bottom surface of the nanocube arrays as two equivalent interfaces with different frequency-dependent polarizability, thin film interference calculations can be established using modified Fresnel equations [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…The surface plasmon waves around the two particles are generated from the electric eld superposition between these waves. Superposing plasmon intensities of two AuNPs with an initial phase difference ( ) as (or ) gives us a quantum superposition of , and consequently yields complex and cumulative superposing plasmon intensities [33]. This can be deduced from Eq.…”
Section: Two-particle Interferencementioning
confidence: 99%
“…Among these, strong coupling between photonic cavities and plasmons have been of increasing interest [4,[6][7][8][9][10] since the first demonstration between localized plasmons in nanowire pairs and photonic Fabry-Pérot (F-P) microcavity modes by Ameling and Giessen in 2010 [11]. By combining plasmonic nanostructures and photonic microcavities, it has been demonstrated that the sensing properties of localized plasmon sensors can be enhanced [12][13][14], that up to two-fold enhancement increase can be achieved compared to that without using the cavity [15], that large Rabi splitting can be obtained by embedding nanoparticle-WS 2 heterostructure in an optical microcavity [16,17], and that both peak splitting and peak locking behaviors can be observed [18].…”
Section: Introductionmentioning
confidence: 99%